Nonlinear model predictive control-based optimal energy management for hybrid electric aircraft considering aerodynamics-propulsion coupling effects - Zhang, Jinning; Roumeliotis, Ioannis; Zolotas, Argyrios (IEEE, 2021)
Hybrid electric propulsion systems have been identified as the feasible solutions for regional jets and narrow-body aircrafts to reduce block fuel burn, emissions, and operating cost. In this paper, a Nonlinear Model Predictive Control based optimal energy management scheme (MPC-EMS) has been proposed to minimize the block fuel burn during flight. Firstly, the Artificial Neural Network (ANN) model is adopted to predict turbofan engine performance, meanwhile gas turbine-electrical powertrain integration is investigated and analyzed for typical operating conditions. Then, by combining a point-mass aircraft dynamic model, nonlinear model predictive control with Cross-Entropy Method (CEM) is proposed to obtain optimal energy management based on a fully coupled aerodynamics-propulsion hybrid electric aircraft model. Besides, this state-constrained optimal control problem is re-formulated as a state-unconstrained problem with penalty function to reduce the computational load. Finally, the proposed MPC-EMS algorithm is applied to Boeing 737-800 aircraft with mechanically parallel hybrid electric propulsion configuration to minimize the block fuel burn and compared with the optimization results using global Genetic Algorithm (GA) based EMS and Equivalent Consumption Minimization Strategy (ECMS). The simulation results indicate that the proposed MPC-EMS can effectively reduce the computational time compared with Global GA-based EMS while achieving global optimization performance with only a minor difference of 1.71% of block fuel burn and emissions reductions.
Keywords: Hybrid electric aircraft; Energy management strategy; Nonlinear model predictive control; Aerodynamic-propulsion coupling; Cross-Entropy Method